The Importance of Leasehold Forestry in Karnali Province, Nepal (Surkhet Journal, 2025)
This study examines the role of leasehold forestry in Karnali Province, Nepal, Highlighting its contributions to environmental sustainability, economic development and community empowerment. By analyzing various socio-economic impacts of the importance of sustainable forest management practices and the need for supportive policies to enhance community livelihoods, this article illustrates the strategies for improving leasehold forestry in Karnali, including capacity building and market access. It discusses the importance of leasehold forestry in Karnali Provance to address persistent poverty, food insecurity, and environmental degradation. The findings show that leasehold forestry has been promoted as a means to improve household livelihoods, empower marginalized groups, and restore degraded forest land. The study suggests that it is imperative to manage the control of free grazing in leasehold forest natural regeneration with new plantation, mobilizing indigenous communities, generation of cash income of beneficiaries from livestock composition of household expenditure with increased expenditure on health and education encouraging forest user groups saving. The study found that compared to men, women’s participations in harvesting forest product was higher, thought women had less control on the income generated from the sale of those products. The land leased to ultra poor and landless household groups was poorer quality than that of other groups. Based on the findings of the evaluation, it is concluded that the study has been contributing to restoring ecological balance and poverty reduction in the study areas of Nepal.